Sucla2 Knock‐Out in Skeletal Muscle Yields Mouse Model of Mitochondrial Myopathy With Muscle Type–Specific Phenotypes - Makayla S. Lancaster; Paul Hafen; Andrew S. Law; Catalina Matias; Timothy Meyer; Kathryn Fischer; Marcus Miller; Chunhai Hao; Patrick Gillespie; David McKinzie; Jeffrey J. Brault; Brett H. Graham (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Pathogenic variants in subunits of succinyl‐CoA synthetase (SCS) are associated with mitochondrial encephalomyopathy in humans. SCS catalyses the conversion of succinyl‐CoA to succinate coupled with substrate‐level phosphorylation of either ADP or GDP in the TCA cycle. This report presents a muscle‐specific conditional knock‐out (KO) mouse model of Sucla2, the ADP‐specific beta subunit of SCS, generating a novel in vivo model of mitochondrial myopathy. Methods The mouse model was generated using the Cre‐Lox system, with the human skeletal actin (HSA) promoter driving Cre‐recombination of a CRISPR‐Cas9–generated Sucla2 floxed allele within skeletal muscle. Inactivation of Sucla2 was validated using RT‐qPCR and western blot, and both enzyme activity and serum metabolites were quantified by mass spectrometry. To characterize the model in vivo, whole‐body phenotyping was conducted, with mice undergoing a panel of strength and locomotor behavioural assays. Additionally, ex vivo contractility experiments were performed on the soleus (SOL) and extensor digitorum longus (EDL) muscles. SOL and EDL cryosections were also subject to imaging analyses to assess muscle fibre‐specific phenotypes. Results Molecular validation confirmed 68% reduction of Sucla2 transcript within the mutant skeletal muscle (p < 0.001) and 95% functionally reduced SUCLA2 protein (p < 0.0001). By 3 weeks of age, Sucla2 KO mice were 44% the size of controls by body weight (p < 0.0001). Mutant mice also exhibited 34%–40% reduced grip strength (p < 0.01) and reduced spontaneous exercise, spending about 88% less cumulative time on a running wheel (p < 0.0001). Contractile function was also perturbed in a muscle‐specific manner; although no genotype‐specific deficiencies were seen in EDL function, SUCLA2‐deficient SOL muscles generated 40% less specific tetanic force (p < 0.0001), alongside slower contraction and relaxation rates (p < 0.001). Similarly, a SOL‐specific threefold increase in mitochondria (p < 0.0001) was observed, with qualitatively increased staining for both COX and SDH, and the proportion of Type 1 myosin heavy chain expressing fibres within the SOL was nearly doubled (95% increase, p < 0.0001) in the Sucla2 KO mice compared with that in controls. Conclusions SUCLA2 loss within murine skeletal muscle yields a model of SCS‐deficient mitochondrial myopathy with reduced body weight, muscle weakness and exercise intolerance. Physiological and morphological analyses of hindlimb muscles showed remarkable differences in ex vivo function and cellular consequences between the EDL and SOL muscles, with SOL muscles significantly more impacted by Sucla2 inactivation. This novel model will provide an invaluable tool for investigations of muscle‐specific and fibre type–specific pathogenic mechanisms to better understand SCS‐deficient myopathy.